2021
DOI: 10.31817/vjas.2021.4.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment Process on Mechanical Properties of Medium Carbon Steel

Abstract: In order to select an appropriate heat treatment process for an industrial application of S45C medium carbon steel, it is necessary to investigate the influence of technological parameters during the heat treatment process such as heating temperature, holding time and cooling medium on the microstructure and mechanical properties. In this study, the experiments were conducted in various heating temperatures, holding times and cooling mediums for specimens made of S45C steel. Then, the relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many studies have shown the influence of heat treatment parameters (temperature, holding time, cooling) on the microstructure. In the study [1], the authors conducted experiments with different temperatures, holding times, and cooling environments for S45C steel. The results show that temperature and cooling environment strongly affect the microstructure of this steel, leading to significant changes in hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the influence of heat treatment parameters (temperature, holding time, cooling) on the microstructure. In the study [1], the authors conducted experiments with different temperatures, holding times, and cooling environments for S45C steel. The results show that temperature and cooling environment strongly affect the microstructure of this steel, leading to significant changes in hardness.…”
Section: Introductionmentioning
confidence: 99%